A Three-Dimensional Model of the Effective Electromechanical Impedance for an Embedded PZT Transducer. (31st December 2013) - Zuo, Chunyuan; Feng, Xin; Zhou, Jing
Abstract : A three-dimensional model of the effective electromechanical impedance for an embedded PZT transducer is proposed by considering the interaction between a PZT patch and a host structure. By introducing an effective mechanical impedance, the coupled electromechanical admittance formulations are derived using the piezoelectric constitutive equations. Then, a modified methodology for monitoring structure changes using an electromechanical impedance (EMI) technique is proposed. In the proposed method, the changes in the host structure are monitored by using the "active" part associated with the structural mechanical impedance, which is extracted from the measured raw admittance signatures. The strength gain of a concrete beam with embedded PZT transducers during the curing age was monitored with the proposed methodology. The experimental results demonstrate that the use of the "active" part is more sensitive as opposed to the raw admittance signatures for structural health monitoring (SHM).